Comparative analysis of stormwater management techniques: case study of Malaysia, Japan and the Netherlands - Ahmad Khairi, Ameera Nazeerah; Ponrahono, Zakiah; Sahrir, Syazwani (IIUM Press, 2024)
Climate change and rapid urbanisation lead to the reduction of green spaces due to infrastructure development to meet the growing population's demands. As a result, the increase in impervious surfaces and inadequate drainage systems leads to flooding problems. As one of the tropical countries with heavy annual precipitation, Malaysia has gained attention for global warming issues. The purpose of the study is to analyse stormwater management practices in several developed countries, such as the Netherlands and Japan, compared to Malaysian practices. Case studies were extracted from the literature findings, allowing the adoption and utilisation of practices from developed countries in Malaysia. The research revealed that both case studies, Tokyo's G-Cans Project and the Netherlands' Delta Works, implemented several techniques that offer significant potential for flood mitigation projects in Malaysia. However, the data reveal that previous pavements, swales, and detention ponds serve as stormwater infrastructure in all three nations. Both developed countries have encouraged the implementation of green roofs, but Malaysia continues to face resource limitations and new exposure issues. The Malaysian government should contemplate expanding the number of monitoring stations to enhance data accuracy and emulate Japan's innovative use of artificial intelligence (AI) for future flood prediction. Current issues in Malaysia, such as sinkhole incidents and flooding, require the government to act efficiently and regularly monitor. In summary, Malaysia still needs to catch up in stormwater management and flood mitigation, necessitating the adoption of practices from advanced countries for improved future development.